Свобода та обов’язковість виконання договору в цивільному праві України - Жорнокуй, Ю. М.; Zhornokui, Yu. M.; Жорнокуй Юрій Михайлович (Вісник Харківського національного університету внутрішніх справ. – 2022. – № 4 (99). – С. 69-80, 2022)
Проаналізовано законодавство України, а також доктринальні підходи та судову практику щодо розуміння свободи й обов’язковості виконання договору в цивільному праві України. Наголошено, що законодавство багато в чому створює ситуацію для обмеження дії принципу свободи договору. При цьому ні законодавство, ні правозастосовна практика не містять жодних застережень, які б дозволили змінити відповідний стан справ на користь засад диспозитивності регулювання приватноправових відносин. Зауважено, що принцип свободи договору в межах цивільно-правових відносин не має абсолютного характеру. Акцентовано увагу на тому, що законодавство, крім обов’язковості виконання договору, передбачає також випадки звільнення сторін договору від виконання своїх обов’язків (від обов’язковості договору).

An analysis of the legislation of Ukraine, as well as doctrinal approaches and judicial practice regarding the understanding of freedom and obligation to perform a contract in the civil law of Ukraine, has been carried out. It has been concluded that the legislation in many respects creates situation where the principle of freedom of contract is restricted. At the same time, neither legislation nor law-enforcement practice contain any reservations that would allow changing the relevant state of affairs in favor of the principles of dispositive regulation of private law relations. It has been noted that the principle of freedom of contract within civil law relations does not have an absolute nature, which is confirmed by the provisions of civil legislation that ensure the procedure for conclusion, execution and responsibility for individual contractual structures regulated by the Civil Code of Ukraine (e.g., a public contract, an accession agreement, etc.), as well as relations connected with consumer protection. Based on the conducted research, it has been proposed to single out two main models for restriction of contract freedom: 1) establishment of direct restrictions by the state, by indicating which specific conditions the parties are forbidden to agree on in the contract; 2) consolidation of general evaluation standards that the transaction and its terms must meet by the legislator or higher courts at the level of law or law enforcement practice. Attention has been focused on the fact that the ability to realize interests under one’s own responsibility is the basis of the contract, and that contractual binding and responsibility are its inevitable consequences. Despite the fact that the legislation provides for the obligation to perform the contract (Article 629 of the Civil Code of Ukraine), it also provides for cases of contract parties’ release from the performance of their obligations (from the obligation of the contract).

Проанализированы законодательство Украины, а также доктринальные подходы и судебная практика по пониманию свободы и обязательности выполнения договора в гражданском праве Украины. Отмечено, что законодательство во многом создает ситуацию для ограничения действия принципа свободы договора. При этом ни законодательство, ни правоприменительная практика не содержат никаких оговорок, позволяющих изменить соответствующее положение дел в пользу основ диспозитивности регулирования частноправовых отношений. Замечено, что принцип свободы договора в пределах гражданско-правовых отношений не носит абсолютного характера. Акцентировано внимание на том, что законодательство, помимо обязательности исполнения договора, предусматривает случаи освобождения сторон договора от исполнения своих обязанностей (от обязательности договора).
Freedom and obligatory performance of a contract in the civil law of Ukraine
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; договір; contract; договор; свобода договору; freedom of contract; свобода договора; принципи цивільного права; principles of civil law; принципы гражданского права; обов’язковість виконання договору; obligation to perform the contract; обязательность выполнения договора; суб’єкти цивільного права; subjects of civil law; субъекты гражданского права